The Exploitation of Street Children by Parents in Pasir Koja of Bandung City - Nurfaizi, Muhammad Alfi; Iqbal, Muhammad; Octavia, Vera (TEMALI : Jurnal Pembangunan Sosial, 2022)
Street children are a social phenomenon that is often found in various areas in the city of Bandung. Typically children enjoy playing, but they spend most of their time on the streets to earn money, which should have been the duty and obligation of their parents. The qualitative research method describes the problem by collecting data directly through interviews and observation. The purpose of this study is to find out the background and reality of life that street children go through and to find out about the factors that cause them to take to the streets to earn money. The results obtained in the field show that the presence of street children is driven by the exploitation of their children by parents. In reality, parents use their children to make money on the streets of Pasir Koja, either by begging or singing. Basically, the age of these children is still very young, this is what parents take advantage of, because young children will more easily get people's attention to give them money.